The Incentive Costs of Welfare Judgments - Thomas Daske (ZBW - Leibniz Information Centre for Economics, 2021)
This paper draws an incentive-theoretical perspective on the concept of social welfare. In a simple mechanism-design framework, agents' interpersonal preferences and private payoffs are all subject to asymmetric information. Under reasonable normative assumptions, the following result is established: A policy can be implemented with a budget-balanced mechanism if and only if it is consistent with materialistic utilitarianism, which seeks to maximize aggregate material wealth, not utility. Any other policy, to be implementable, must violate budget balance and therefore comes at incentive costs. The corresponding mechanism is virtually unique, which allows for conclusions upon distributive and procedural justice.
Keywords: C78; D60; D82; 330; mechanism design; social welfare; distributive justice; procedural justice; utilitarianism; dictatorship